External Skeletal Fixator Intramedullary Pin “Tie-in” for the Repair of Comminuted Tibial Fracture in a Brazilian Fox (Pseudalopex vetulus) - Barranco, Guilherme Henrique Fernandes; Barssalho, Michelly Amanda; Almeida, Diego Alaska; Ferreira, Joana Zafalon; Fernandez, Sthephanie; Cruvinel, Tatiana Morosini de Andrade; Rossetto, Victor José Vieira (Acta Scientiae Veterinariae, 2016)
Background: The Brazilian fox (Pseudalopex vetulus, Lund 1842) is a naturally endemic specie of the Brazilian savana vegetation. Due to the rapid destruction of its habitat, the specie is considered “vulnerable” and subject to different kinds of trauma that usually results in fractures and dislocations. Among the methods of fractures fxation, highlights the external skeletal fxator intramedullary pin “tie-in” which consists of the intramedullary pin associated to the external fxator. The aim of the present report was to describe the case of a Brazilian fox with a comminuted tibial fracture, submitted to osteosynthesis using an external skeletal fxator intramedullary pin “tie-in”. Case: It was attended an exemplar of Pseudalopex vetulus, male, young adult, with 3.9 kg body weight and history of functional impotence of the left hindlimb. At the physical and orthopedic evaluations were observed loss of bone continuity and crepitus in tibial region, and the presence of a contaminated lacerating skin wound about 3 cm in diameter in the lateral side of the injured limb. Craniocaudal and mediolateral radiographic projections of the left hindlimb revealed the presence of a complete comminuted fracture at the proximal and distal shaft of the left tibia; and a complete transverse fracture at mid shaft of the left fbula. Due to this, the animal was submitted to fracture fxation using an external skeletal fxator intramedullary pin “tie-in”. For the surgical procedure, broad trichotomy and antisepsis of the left hindlimb were performed, followed by a longitudinal incision on the medial side of the tibia. After bone fragments identifcation, was realized the retrograde positioning of a Steinmann pin of 3.0 mm in diameter toward the proximal epiphysis. Subsequently, the pin was externalized in the parapatelar region and then replaced toward the distal epiphysis. The intramedullary pin was not cut, but folded and attached to the transcortical pins of the unilateral external skeletal fxator using polymethylmethacrylate acrylic resin. For the unilateral external skeletal fxator were placed four Kirschner pin of 1.5 mm in diameter. Of these, two pins were placed at the proximal bone segment of the fracture, and two at the distal one. The central bone segment was not transfxed by pins. Radiographic postoperative examination revealed fracture reduction with good alignment of the bone fragments. The metallic implants were also well positioned. Bone healing was verifed at 150 days postoperatively. At this moment, radiographic examination revealed calcifed and ossifed bone callus, and the maintenance of bone axis.The animal was reintroduced to nature. Discussion: The external skeletal fxator intramedullary pin “tie-in” features biomechanical superiority to both intramedullary and external skeletal fxator pin, since it resists to rotational, bending and axial forces that act at the fracture. Additionally, it is a less expensive fracture fxation method, especially when replacing the lateral connecting rod by polymethylmethacrylate acrylic resin. It was concluded that the external skeletal fxator intramedullary pin “tie-in”can be considered viable in small wild mammals, such as the Brazilian fox (Pseudalopex vetulus), since it enabled the bone healing and the limb functionality. Further studies with a greater number of individuals, however, are necessary to evaluate the real applicability of the fracture fxation method. Keywords: traumatology, osteosynthesis, wild animals.